Ecological inputs in silk screen printing: peruvian case - Rojas Lazo, Oswaldo (2011)
The silk screen printing used by the micro and small businesses (MYPE for its acronym in Spanish) of Peru, is characterized for being artisanal, which means that they use clean technologies, however, they don’t use ecological inputs. Peru is a rich country in the tradition of use of natural inks from the time of inca and preinca’s cultures. At present mentioned tradition is limited to clothes elaborated for foreign tourists and in far places of difficult access. In the essays made to obtain a natural ink for the printing process, tests have been made with eucalyptus (Eucalyptus), getting good results with the system consisting of the extract of eucalyptus leaves and starch as vehicle.